Patriarchy Reinvented? Spiritual Parenting' within African Pentecostalism in Zimbabwe - Dube, Zorodzai (Verbum et ecclesia, 2018)
How do we explain the emergency of spiritual parenting' concept within African Pentecostal churches especially in urban Zimbabwe? From ethnographic studies done in Harare, Zimbabwe, these seem to usurp the traditional role of motherhood and fatherhood of counselling, instructing, protecting, guidance and all the functions of parenthood. This study explains the emergence of spiritual parenting as a development plausibly explainable through social variables such as i) the disintegration of traditional patriarchal values due to growing urbanisation and ii) socio-economic insecurities that seem to produce alternative kinship ties. Taking a constructive postmodern approach, the concept of spiritual parenting is plausibly explained as providing alternative fatherhood' spaces, thus implicitly re-invent traditional patriarchal models under the guise of Christian spiritualities. Intradisciplinary and/or interdisciplinary implications: Using social scientific approaches, the study explains the emergence of particular spiritualties in modern African Christianity, viewing such spiritualties as influenced by particular explanatory social variables. It argues that new spiritualties and practices within African Pentecostalism may be plausibly explained vis-à-vis from particular cultural realities.